Increase in Neopterin Serum Levels Based On Exposure Duration of Silica Dust in Marble Industry Workers - Suryaman, Rachmat; Astuti, Tri Wahju; Rakhma, Sastia; Sari, Fitri Indah (Jurnal Respirologi Indonesia, 2025)
Background: Workers in the marble industry face the risk of exposure to dust containing silica crystals in their workplace, a substantial contributor to most occupational lung diseases. Neopterin, an early biomarker of the cellular immune response, is recognized for its association with silica dust exposure. According to a previous study, neopterin levels significantly increased in workers with silicosis compared to controls with no exposure to marble dust. This study aims to analyze changes in neopterin levels based on the duration of silica dust exposure among marble workers. Methods: The study design is an analytical cross-sectional study with a subject pool comprising 32 marble industry workers, categorized into 4 groups based on the duration of exposure: 1-5 years, 5-10 years, >10 years, and control. A comparative analysis was conducted with a control group. Neopterin levels were assessed through the utilization of the Human Neopterin ELISA kit. Analysis using T-tests, ANOVA, and Pearson correlation tests, providing a comprehensive evaluation of the impact of exposure duration. Results: Chest X-ray shows normal results in a routine procedure for most workers. When compared to the control groups, there was a significant increase in serum neopterin levels in all workers. A significant increase was also obtained in neopterin levels among workers with over 5 and over 10 years of exposure. Also, a significant positive correlation between neopterin levels and the duration of exposure. But, among smoker workers, neopterin levels and the Brinkman index level do not show a significant increase. Notably, workers who use nonstandard face masks demonstrate no significant difference in neopterin levels. Conclusion: As marble industry workers are exposed to silica dust for an extended period, there is a corresponding increase in their serum neopterin levels. The duration of silica dust exposure, specifically exceeding five years, significantly influences the elevation of serum neopterin levels.